2018
DOI: 10.1111/ced.13561
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum interleukin-17A and clinical response to tofacitinib and etanercept in moderate to severe psoriasis

Abstract: SummaryBackground. Psoriasis is a systemic inflammatory disease with a pathophysiology involving interleukin (IL)-17. Tofacitinib is an oral Janus kinase inhibitor. Etanercept is a tumour necrosis factor-a inhibitor used in the treatment of psoriasis. Neither agent inhibits IL-17 directly. Aim. To evaluate correlations between circulating IL-17A and clinical efficacy in patients with psoriasis treated with tofacitinib or etanercept. Methods. Serum concentrations of IL-17A homodimer and IL-17A/F heterodimer wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…Moreover, they concluded that an increase in IL-17A level even with 1pg/ml predisposed for severe psoriasis [56]. Also, Fitz et al drew attention to the value of assessing IL-17 expression profile in psoriatic patients before commencing an anti-cytokine therapy [57].…”
Section: Of Psoriasis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they concluded that an increase in IL-17A level even with 1pg/ml predisposed for severe psoriasis [56]. Also, Fitz et al drew attention to the value of assessing IL-17 expression profile in psoriatic patients before commencing an anti-cytokine therapy [57].…”
Section: Of Psoriasis Treatmentmentioning
confidence: 99%
“…Również Fitz i wsp. zwrócili uwagę na znaczenie określania profilu ekspresji IL-17 u pacjentów z łuszczycą przed rozpoczęciem terapii antycytokinowej [57].…”
Section: Conflict Of Interestunclassified
“…Etanercept shows an ability to neutralize only a soluble TNF-α, whereas adalimumab neutralizes both free and membrane-bound TNF-α [4,7,9]. Moreover, it is indicated that serum IL-17 concentration prior to a therapy with anti-cytokine drugs, including etanercept, determines the odds for the therapy success [19]. Al-Gareeb et al observed also a lack of adequate response to etanercept in patients suffering from rheumatoid arthritis [20].…”
Section: Omówieniementioning
confidence: 99%
“…Etanercept ma zdolność neutralizowania tylko rozpuszczonej formy TNF-α, a adalimumab neutralizuje zarówno wolną, jak i związaną z błoną komórkową formę TNF-α [4,7,9]. Wskazuje się również, że stężenie IL-17 w surowicy przed rozpoczęciem terapii lekami antycytokinowymi, w tym etanerceptem, określa szansę powodzenia terapii [19]. Al-Gareeb i wsp.…”
Section: Omówienieunclassified
“…Учитывая тот факт, что концентрация ИЛ-17 и АТ к рТТГ напрямую коррелирует с клиническими проявлениями активности ЭОП, их совместное определение в сыворотке крови может дать дополнительную информацию о состоянии аутоиммунитета и использоваться для прогноза течения данного заболевания. Полученные данные по ИЛ-17 сопоста-вимы с результатами исследований как при других аутоиммунных заболеваниях [7,8,15], так и при ЭОП [16].…”
Section: обсуждение основного результата исследованияunclassified